UTERINE MYOMA (XKT–10:D26) AND MODERN APPROACH TO ITS DIAGNOSIS AND TREATMENT (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article provides an analysis of uterine quality tumor, i.e. uterine myoma coexistence with other extragenital diseases in women, meeting with various gynecological diseases of genital organs, and its complications. One of the modern diagnostic methods in the prevention and prognosis of uterine fibroids in women is the method of determining oncomarkers in blood serum